CK2 Phosphorylating I2PP2A/SET Mediates Tau Pathology and Cognitive Impairment - Zhang, Qing; Xia, Yiyuan; Wang, Yongjun; Shentu, Yangping; Zeng, Kuan; Mahaman, Yacoubou A. R.; Huang, Fang; Wu, Mengjuan; Ke, Dan; Wang, Qun; Zhang, Bin; Liu, Rong; et al. (Frontiers in Molecular Neuroscience, 2018)
Casein kinase 2 (CK2) is highly activated in Alzheimer disease (AD) and is associated with neurofibrillary tangles formation. Phosphorylated SET, a potent PP2A inhibitor, mediates tau hyperphosphorylation in AD. However, whether CK2 phosphorylates SET and regulates tau pathological phosphorylation in AD remains unclear. Here we show that CK2 phosphorylating SET at Ser9 induced tau hyperphosphorylation in AD. We found that either Aβ treatment or tau overexpression stimulated CK2 activation leading to SET Ser9 hyperphosphorylation in neurons and animal models, while inhibition of CK2 by TBB abolished this event. Overexpression of CK2 in mouse hippocampus via virus injection induced cognitive deficit associated with SET Ser9 hyperphosphorylation. Injection of SET Ser9 phosphorylation mimetic mutant induced tau pathology and behavior impairments. Conversely co-injection of non-phosphorylated SET S9A with CK2 abolished the CK2 overexpression-induced AD pathology and cognitive deficit. Together, our data demonstrate that CK2 phosphorylates SET at Ser9 leading to SET cytoplasmic translocation and inhibition of PP2A resulting in tau pathology and cognitive impairments.